Naravna in kulturna dediščina skozi perspektive otrok - Turk Niskač, Barbara (Traditiones (Ljubljana), 2013)
Studies on heritage as a social construct usually focus on adults. However, I was interested in children's perception of natural and cultural heritage in their local environment. I asked primary school children to take photographs of their surroundings; this was followed by interviews in which they explained what they captured. I was interested in how children perceive heritage and what meanings they attribute to it. This article sheds an alternative light on the understanding of heritage through children's perspectives.
Keywords: ethnology; Kulturna dediščina; Naravna dediščina; folk culture; Narodni parki; cultural heritage; natural heritage; Triglavski narodni park; anthropology of childhood; Etnologija; Ljudska kultura; Slovenska ljudska kultura; Antropologija otroštva; Vizualna antropologija; Triglav National Park; otroci; child; Bohinj